Determining a Short Form Montreal Cognitive Assessment (s-MoCA) Czech Version: Validity in Mild Cognitive Impairment Parkinson's Disease and Cross-Cultural Comparison. (December 2020) - Bezdicek, Ondrej; Červenková, Markéta; Moore, Tyler M.; Stepankova Georgi, Hana; Sulc, Zdenek; Wolk, David A.; Weintraub, Daniel A.; Moberg, Paul J.; Jech, Robert; Kopecek, Miloslav; Roalf, David R.
The Montreal Cognitive Assessment (MoCA) is one of the most common screening instruments for mild cognitive impairment. However, the standard MoCA is approximately two times longer to administer than the Mini-Mental State Examination. A total of 699 Czech and 175 American participants received the standard MoCA Czech and English versions and in the clinical part, a sample of 102 nondemented patients with Parkinson's disease (PD). We created a validated Czech short version (s-MoCA-CZ) from the original using item response theory. As expected, s-MoCA-CZ scores were highly correlated with the standard version (Pearson r = .94, p < .001). s-MoCA-CZ also had 80% classification accuracy in the differentiation of PD mild cognitive impairment from PD without impairment. The s-MoCA-CZ, a brief screening tool, is shorter to administer than the standard MoCA. It provides high-classification accuracy for PD mild cognitive impairment and is equivalent to that of the standard MoCA-CZ.